The Image Looks Back / PHOTO2020 - Gray, Michael (2020)
This series constituted the only work from a Western Australian artist included in PHOTO2020, a major new international festival of photography that was delivered over 25 cultural institutions, museums, galleries and universities across Melbourne. The inaugural theme invited artists, curators, writers and academics to interrogate the relationship between photography and truth in the post-internet age.